Control of mobile robot using fractional order PIλDμ controller - Boucetta, Younes; Ayad, Redouane; Ahmed-Foitih, Zoubir (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2019)
The ideal example for studying complex systems with non-holonomic constraints is mobile-wheeled robots. In this article, we study the problem of trajectory tracking of mobile robot unicycle type. To resolve this type of problem a fractional-order control technique is proposed. The main objective of this control method is to design a robust tracking controller to eliminate disturbances. The mathematical model of the mobile robot taken explicitly into account their dynamics is used to calculate the desired linear and angular velocities. To adjust the controller optimal parameters the particle swarm optimization (PSO) algorithm is utilized. The simulation results allowed us to demonstrate the efficiency and robustness of this technique on non-holonomic systems in the form of chained chains.